XVI World Congress of Sociology. A Look from the Inside - Juozeliūnienė, Irena (Sociologija. Mintis ir veiksmas, 2007)
A look on XVI ISA World Congress of Sociology.
Keywords: XVI ISA World Congress of Sociology